Strategi Keamanan Transaksi Elektronik dalam Pelayanan Publik Berbasis E-Government - Dini Andriani; Abd. Haris; Sumardi (PENA BANGSA: Bisnis dan Tata Kelola Publik Adaptif, 2025)
Digital transformation has driven significant changes in the delivery of public services. In the era of e-government, service digitalization is aimed at creating a bureaucracy that is more transparent, efficient, and responsive. One of the most complex stages in e-government is transact, namely the phase of data exchange and electronic transactions between citizens and the government. The high sensitivity of data at this stage makes security a crucial factor. This study aims to analyze electronic transaction security strategies in e-government comprehensively. The research method used is a descriptive qualitative approach with a literature study (library research) method. The findings show that electronic transaction security in e-government is supported by the use of various technologies, including encryption, digital signatures, Public Key Infrastructure (PKI), firewalls, biometric authentication, and blockchain to ensure data confidentiality and reliability, as well as strong regulations such as the Electronic Information and Transactions Law (UU ITE) and the Personal Data Protection Law. In addition, the readiness of human resources, both from the government and the public, is also a determining factor for success, particularly in the areas of digital literacy, information security training, and a risk-aware work culture. These three aspects complement one another in building a reliable security system.